Factitious Disorder Masquerading as a Life-Threatening Anaphylaxis - Resha Khanal MD; Selin Sendil MD; Sharad Oli MBBS; Binita Bhandari MD; Anas Atrash MD (SAGE Publishing, 2021)
Factitious disorder is a psychiatric disorder in which sufferers intentionally fabricate physical or psychological symptoms in order to assume the role of the patient, without any obvious gain. We present a case of a 23-year-old female with chronic urticaria who presented with dyspnea, dysphasia, mild generalized erythema, abdominal cramps, and headache. She was tachypneic and hypotensive. This was her third admission with similar symptoms within the last 7 months. Tryptase, complement, anti-SM/RNP, Sjogren, Scl-70, C3, and C4 were negative. Computed tomography-guided bone marrow biopsy showed no mast cells. Flow cytometry did not show any immunophenotypic reaction. Other possible differentials including pregnancy, autoimmune disorders, and infections including hepatitis, thyroid disorder, and age-related malignancies were ruled out. After a thorough review, malingering disorder was ruled out, but we noticed the patient's intent of assuming a sick role. Later, the patient was diagnosed with major depressive disorder. Factitious anaphylaxis can present with multiple presentations including a life-threatening condition that mimics true anaphylaxis. A better approach would be thorough clinical evaluation and early multidisciplinary involvement. This case highlights the importance of further evidence-based studies in factitious disorder to decrease the disease burden and reduce the health care cost.